Understanding Italy's stagnation - Max Krahé (Dezernat Zukunft e.V., 2023)
Italy's economic stagnation is a matter of fiscal, national, and European concern. Since a good remedy requires an accurate diagnosis, this paper summarises, compares, and evaluates the main explanations for this stagnation. After describing Italy's recent economic record, the paper reviews three families of explanations: "unwillingness to reform" accounts, monetary integration accounts, and accounts that prioritise the firm-level perspective. Concluding that, taken by themselves, none of these explanations provide a fully convincing account, a synthesis of their most promising elements follows. In this synthesis, the paper argues that Italy's recent stagnation can be traced back to two key moments: first, a failed attempt during the 1990s and early 2000s to overcome the growth slowdown of the 1970s and 1980s. Guided by the ideas of their time and the desire to meet the Maastricht convergence criteria, policy-makers chose a mix of market-liberalising reforms and demand suppression. Though well-intentioned, this mix proved counterproductive, lowering investment- and human capital growth and deepening the growth slowdown it was meant to remedy. The second key moment was the retention of this policy mix in the late 2000s and early 2010s. In the wake of 2008, once investors realised that the ECB would not be a conventional lender of last resort, spreads on Italian government bonds increased, and although the macro-financial architecture of the Eurozone was reformed, these reforms militated towards a doubling-down on Italy's pre-crisis policy mix. Subject to these pressures, policy-makers retained the broad strokes of the earlier policy mix, even after its ineffectiveness had become apparent. While this paper does not develop proposals for a new reform mix, its diagnosis implies that any credible reform package must tackle the deep roots of Italy's stagnation without repeating the investment-suppressing mistakes of the last 30 years. In light of this, positive conditionality - i.e. conditions that unlock additional resources, as with NextGenEU - with a focus on companies, institutions and investment, may be a promising way forward.
Keywords: 330